Genetic and environmental influences on beef cattle production in Zambia. 2. Live weights for age of purebred and reciprocally crossbred progeny - Thorpe, W.R.; Cruickshank, D.K.R.; Thompson, R. (Cambridge University Press, 1980)
Live weights from birth to 3.5 years are reported for beef cattle reared under ranching conditions in Zambia. The 809 cattle were purebred Africanders, Angonis, Barotses and Improved Borans and the reciprocal crossbreds of the latter three breeds born in 2 years. All animals born in the 1st year and half the males born in the 2nd year grazed natural grassland. The remaining males and all females born in the 2nd year received, in addition, dry season supplementary feed from 1.5 years of age. The interaction of genotype with year-of -birth was important but not the interactions of genotype with management or sex. Purebred progeny of the introduced Africander breed were heavier than the progeny of the indigenous Angoni and Barotse breeds in both year-of-birth groups, but only heavier than progeny of the introduced Boran breed in the first group. On average, the Africander progeny had live-weight advantages of about 16% and 10%, and the Boran progeny advantages of about 12.5% and 5.5% over the purebred Angoni and Barotse progeny respectively. Heterosis estimates tended to increase with age, reaching levels of about 5 to 6% in the Barotse/Boran crosses at and after 1.5 years. Heterosis was not shown by the other crosses. The Barotse and Boran breeds had similar maternal effects which were superior to those of the Angoni breed.